2020
DOI: 10.1101/2020.09.16.298539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective connectivity and spatial selectivity-dependent fMRI changes elicited by microstimulation of pulvinar and LIP

Abstract: The thalamic pulvinar and the lateral intraparietal area (LIP) share reciprocal anatomical connections and are part of an extensive cortical and subcortical network involved in spatial attention and oculomotor processing. The goal of this study was to compare the effective connectivity of dorsal pulvinar (dPul) and LIP and to probe the dependency of microstimulation effects on task demands and spatial tuning properties of a given brain region. To this end, we applied unilateral electrical microstimulation in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 143 publications
(354 reference statements)
4
8
0
Order By: Relevance
“…In addition, the pulvinar is likely to influence the dorsal stream of visual processing (Milner & Goodale, 1995;Ungerleider & Mishkin, 1982), given its reciprocal connections with the lateral intraparietal cortex (Kagan et al, 2021) and its identified contributions to visuospatial attentional task processing, decision-making and multisensory integration (Froesel et al, 2021;Komura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pulvinar is likely to influence the dorsal stream of visual processing (Milner & Goodale, 1995;Ungerleider & Mishkin, 1982), given its reciprocal connections with the lateral intraparietal cortex (Kagan et al, 2021) and its identified contributions to visuospatial attentional task processing, decision-making and multisensory integration (Froesel et al, 2021;Komura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing results presented in the current work with the few previous studies on visual and oculomotor motor properties of the pulvinar, it is important to note that most studies in the dorsal pulvinar recorded from the dorsomedial division of the lateral pulvinar. This division is currently denoted as PLdm (Kaas and Lyon 2007; Bridge et al 2015; Kagan et al 2021), or as Pdm in original electrophysiological studies by Robinson, Petersen and colleagues, e.g. (Petersen et al 1985, 1987; Robinson et al 1986; Bender and Youakim 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The guide tube was filled with sterile silicone oil prior to electrode insertion, to ensure smooth electrode travel and to prevent the backflow of cerebrospinal fluid. T1- and T2-weighted scans were co-registered and transformed into “chamber normal” (aligned to the chamber vertical axis) and to anterior commissure – posterior commissure (AC-PC) space for electrode targeting and visualization in BrainVoyagerQX (Brain Innovation, Netherlands) and Planner (Ohayon and Tsao 2012; Kagan et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These nuclei developed together with the association cortices in the course of primate evolution and are reciprocally connected to the parietal and prefrontal cortex, orbitofrontal cortex, insula, cingulate, superior and inferior temporal cortex (Kaas and Lyon, 2007; Preuss, 2007; Kaas and Baldwin, 2020). This extensive connectivity profile identifies the dorsal pulvinar as a unique brain hub well situated to interact with and modulate the circuitry involved in spatial attentional orienting and target selection (Grieve et al, 2000; Sherman and Guillery, 2002; Shipp, 2003; Saalmann and Kastner, 2015; Bourgeois et al, 2020; Kagan et al, 2021). Studies in human patients with unilateral thalamic lesions encompassing the pulvinar demonstrated deficits related to orienting or responding to perceptually or behaviorally salient stimuli in the contralesional hemifield (Danziger et al, 2001; Karnath et al, 2002; Arend et al, 2008b, 2008a; Lucas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%